Genetic variability and population divergence of Rhododendron platypodum Diels in China in the context of conservation - Ma, Lihui; Li, Liubin; Fang, Wen; Dong, Zhi; Liu, Yang; Wang, Chaoying; Xie, Yingzan; Li, Mingyang; Arif, Muhammad; Wang, Haiyang (Frontiers in Forests and Global Change, 2024)
Genetic diversity in endangered species is of special significance in the face of escalating global climate change and alarming biodiversity declines. Rhododendron platypodum Diels, an endangered species endemic to China, is distinguished by its restricted geographical range. This study aimed to explore genetic diversity and differentiation among its populations, gathering samples from all four distribution sites: Jinfo Mountain (JFM), Zhaoyun Mountain (ZYM), Baima Mountain (BMM), and Mao’er Mountain (MEM). We employed 18 pairs of Simple Sequence Repeat (SSR) primers to ascertain the genetic diversity and structural characteristics of these samples and further utilized 19 phenotypic data points to corroborate the differentiation observed among the populations. These primers detected 52 alleles, with the average number of observed alleles (Na) being 2.89, the average number of effective alleles (Ne) being 2.12, the average observed heterozygosity (Ho) being 0.57, and the expected heterozygosity (He) being 0.50. This array of data demonstrates the efficacy of the primers in reflecting R. platypodum’s genetic diversity. SSR-based genetic analysis of the populations yielded Ho, He, and Shannon index (I) values ranging from 0.47 to 0.65, 0.36 to 0.46, and 0.53 to 0.69, respectively. Notably, the ZYM population emerged as the most genetically diverse. Further analysis, incorporating molecular variance, principal component analysis, UPGMA cluster analysis, and structure analysis, highlighted significant genetic differentiation between the Chongqing (BMM, JFM, ZYM) and Guangxi (MEM) populations. Morphological data analysis corroborated these findings. Additionally, marked genetic and morphological distinctions were evident among the three Chongqing populations (BMM, JFM, and ZYM). This suggests that, despite the observed regional differentiation, R. platypodum’s overall genetic diversity is relatively constrained compared to other species within the Rhododendron genus. Consequently, R. platypodum conservation hinges critically on preserving its genetic diversity and protecting its distinct populations.